2014
DOI: 10.1002/ar.23081
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Fur Development in Echidna (Monotremata, Mammalia) Indicate that Spines Precede Hairs in Ontogeny

Abstract: In the primitive mammal echidna, the initial 2-3 generations of skin appendages produced from birth forms spines and only later true hairs appear. Microscopy on preserved museum specimens reveals that the morphogenesis of spines and hairs is similar but that a larger dermal papilla is formed in spines. The growing shaft comprises a medulla surrounded by a cortex and by an external cuticle. A thick inner root sheath made of cornified cells surrounds the growing shaft inside the spine canal that eventually exits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The almost invisible ne hairs on the skin of elephants has been shown to be responsible for up to 23% of the heat dissipation in these animals at low wind speeds, where their thermoregulation needs are greatest 10 . That hair was preceded in evolution by spines was suggested by Alibardi and Rogers (2014) 11 .…”
Section: Introductionmentioning
confidence: 79%
“…The almost invisible ne hairs on the skin of elephants has been shown to be responsible for up to 23% of the heat dissipation in these animals at low wind speeds, where their thermoregulation needs are greatest 10 . That hair was preceded in evolution by spines was suggested by Alibardi and Rogers (2014) 11 .…”
Section: Introductionmentioning
confidence: 79%
“…The results of the present study provide the basis for investigations of the spatio-temporal expression patterns of EDC genes in monotremes, which will be important to fully evaluate the functions of these genes. Previously, histological and immunohistochemical studies have shown similarities between the epidermis of monotremes and therian mammals 56 58 , but comprehensive investigations of the molecular structure of the epidermis and specialized skin appendages of monotremes 37 , 38 , 59 remain to be performed. The design of specific probes and antibodies against EDC proteins (this study), keratins 40 and other epidermal proteins will help to clarify the molecular evolution of the mammalian skin barrier and skin appendages.…”
Section: Discussionmentioning
confidence: 99%
“…The almost invisible fine hairs on the skin of elephants has been shown to be responsible for up to 23% of the heat dissipation in these animals at low wind speeds, where their thermoregulation needs are greatest [ 10 ]. That hair was preceded in evolution by spines was suggested by Alibardi and Rogers [ 11 ].…”
Section: Introductionmentioning
confidence: 92%